Molecular Dynamics Insights into Peptide-Based Tetrodotoxin Delivery Nanostructures - Shenghan Song; Xinyu Xia; Temair Shorty; Tongtong Li; Amy O. Stevens; Chao Zhao; Yi He (Molecules)
Tetrodotoxin (TTX), a potent Site-1 sodium channel blocker (S1SCB), offers highly effective local anesthetic properties with minimal addiction potential. To fully leverage TTX’s capabilities as a local anesthetic, it is crucial to develop a drug delivery system that balances its systemic toxicity with its therapeutic efficacy. Recent studies have shown that peptide mixtures, derived from fragments of Site-1 sodium channel proteins and enhanced with hydrophobic tails (designated MP1 and MP2), can self-assemble into nanostructures that exhibit remarkable sustained-release capabilities for TTX. Despite the profound impact that the addition of a hydrophobic tail has on altering the release behavior of the original peptides, the atomic-level interactions and mechanisms underlying this phenomenon remain poorly understood. In this study, a combination of ColabFold and molecular dynamics (MD) simulations were used to investigate the binding interactions between TTX and the nanostructures formed by MP1 and MP2 at an atomic level. Our findings agree with experimental observations and indicate that the MP1/MP2 nanostructure demonstrates greater stability and higher binding affinity for TTX compared to their non-modified counterparts, P1 and P2. The analysis of the simulations revealed that charged amino acids, specifically aspartic acid (ASP) and glutamic acid (GLU), on the peptides are crucial for strong TTX binding and serve as the primary functional sites. Additionally, the stability of the nanostructure significantly affects TTX binding affinity, elucidating why P1, P2, MP1, and MP2 exhibit different binding capabilities despite containing identical charged residues. The results reported here may provide fundamental information to drive future research and enhance the development of TTX-based drug delivery systems.